Economics of shipping practice and management - Branch, Alan E. (Chapman and Hall, 1982)
It is appropriate that the second edition of this established textbook sold in over 150 countries and regarded by many as the standard work on the subject -should be published at a time of great change in the international shipping industry. This edition reflects such change. It also places considerable emphasis on the need for a professional approach in all areas of shipping practice and management in order to provide the high quality service required to sustain and expand international trade, and will help to establish that professionalism. The book is ideal not only for students preparing for shipping examinations but also for persons employed in shipping companies, ashore and afloat.